(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Gestational Trophoblastic Disease (GTD) represents a spectrum of neoplastic disorders that arise from placental trophoblastic tissue after abnormal fertilization. The exact etiology of gestational trophoblastic disease is yet unknown. It arises from placental villous and extra villous trophoblast. Proper evaluation and appropriate treatment canreduce the complication of GTD. To evaluate the risk factorsfor optimum treatment according to risk group and response to treatment. Materials and methods: This observational cross-sectional study was conducted in Dhaka Medical College Hospital between 27 th April 2019 and 26 th October 2019.A total of fifty patients having Gestational Trophoblastic Disease (GTD) admitted in Department of Obstetrics & Gynecology indoor during study period were included. Follow up of the patients was done who were treated by suction evacuation or chemotherapy. Data were collected from the informant and recorded in structured case report form. Clinical examination and relevant investigation were done meticulously. Data were analyzed by using Statistical Package for Social Science (SPSS) version 22.0. Results: Among 50 patients with gestational trophoblastic disease 10 (20.0%) have below 20 years age group, 28 (56.0%) havebetween 20 and 30 years age and 3(6%) have >40years age group. Mean age ± SD of the responders was25.94 ± 6.97 years and range was 17-45 years. Among them 11 (22.0%) were nulliparous, 39 (78.0%) were multiparous, 11 (22.0%) were primigravida, 10 (20.0%) were 2 nd gravida, 29 (58.0%) were 3 rd gravida and onwards. Out of 50 respondents, 18 (36.0%) had previous history of abortion and 32 (64.0%) had no previous abortion. Economically middle class of socioeconomic status was predominant (e.g., 44%). Among the respondents 46 (92.0%) patients presented with amenorrhea, 48 (96.0%) presented with per vaginal bleeding, 26 (52.0%) presented with per vaginl expulsion of grape like vesicles and 17 (34.0%) presented with abdominal distenstion.76.0% of patients had pretreatment serum b hCG level more than 100000 m IU/ml. Most of cases (46.0%) have more than 20 weeks of uterine size. Theca lutein cysts in adnexa was detected in 23(46.0%) patients, among them size of cyst was 6-8 cm in 28% cases. Most of the patients (70%) have the diagnosis of hydatidiform mole and serum b hCG levelreaches normal range within 6-8 weeks in 80% cases, but in 20% patients developed persistent GTN and 10% patients developed choriocarcinoma. Among the patients 70% treated only by sucction,evauation and curettage, 20% treated only by chemotherapy and 10% need both Sucction, evacuation, curettage followed by chemotherapy. Among the patients who needed chemotherapy 10(66.66%) patients were treated by single agent chemotherapy and 5(33.33%) patients were treated by combination chemotherapy. Conclusions: GTD largely remains an etiologic enigma. The risk factors for the disease are unclear. In this study an attempt has been made to identify some risk factors, clinical presentation and level of serum a bhCG and ultrasound findings of GTD and response to the current mode of treatment. It will also provideinformation about awareness of the disease and it’s monitoring and surveillance. JCMCTA 2023 ; 34 (2) : 8-13